Analisis Film Animasi Spongebob Ditinjau Dari Brand Identity - Putri Wulandari (TUTURRUPA, 2018)
Animation is not a stranger thing especially for children aged 5th-6th years old. Animationhave closely related with childs imagination. So that invite many controversy toward brandimage on a characters. So it’s discussed about that brand image effect on an animation filmcharacters “ Sponge Bob”, how the effects of visualization and brand story in it become aunity. Brand image is not only bring an effect on children, but also affect the children growth.The influence of characters brand image is very big in determining the mindset, character,and imagination. Because all responses is the brand image on a brand character has afocus that serves as an explanatory of a brand, so that brand can have an unique directionand segmentation of the other animation. Brand image have a unity so as form the movie"Sponge Bob" is a brand story as a story which explains the brand image and brand focusas a meeting point, this is what will be a positioning of characters in the film and became afilm that could be a memory for audiences. So that the evolutin of this animated filmcontinues into a attract one than others.